Effect of GATA3 rs3824662 gene polymorphism in Han Chinese children with pre-B-cell acute lymphoblastic leukemia with 10 years follow-up - Chu, Xinran; Qian, Maoxiang; Yang, Jin; Wu, Dong; Gao, Jing; Cao, Lu; Fang, Fang; Pan, Jian; Zhang, Hui; Hu, Shaoyan (Frontiers in Pediatrics, 2023)
Purpose To evaluate the influence of GATA3 rs3824662 on pre-B-cell acute lymphoblastic leukemia (pre-B-cell ALL) susceptibility and long-term prognosis in Han Chinese children with pre-B-cell ALL treated with the CCLG-2008 protocol at the Children’s Hospital of Soochow University. Methods A total of 256 patients with childhood pre-B-cell ALL under the CCLG-2008 protocol were enrolled in this study, and 174 healthy children were used as case controls. GATA3 rs3824662 genotyping was performed using a polymerase chain reaction, followed by Sanger sequencing. The association of genotype with clinical characteristics, treatment response, adverse events, and outcomes were analyzed. Results The A allele frequency of GATA3 rs3824662 in patients with pre-B cell ALL was significantly higher than that in healthy children (OR = 1.41, 95% CI = 1.042–1.908; P = 0.026). Among patients with pre-B-cell ALL, the GATA3 rs3824662 AA genotype was associated with poor prednisolone response and high blast cell burden on day 15 of the induction therapy (P = 0.011 and 0.007, respectively). Patients with the rs3824662 AA variant suffered more episodes of sepsis than those with the CC or CA variants (P = 0.021). The GATA3 rs3824662 AA genotype was significantly associated with sepsis [hazard ratio (HR) = 3.375; P = 0.01]. No significant differences were found in the cumulative incidence of relapse, overall survival, and event-free survival among all genotypes. Conclusion GATA3 rs3824662 was associated with susceptibility in Han Chinese children with pre-B-cell ALL and could be a possible risk factor for poor early treatment response and treatment-related sepsis.